Fade margin estimations for military X-band satellite communication links in tropical region - Badron, Khairayu; Ismail, Ahmad Fadzil; Wan Nordin, Mimi Aminah; Zainal Abidin, Suriza; Ismail, Maszlan; Ooi, Sock Teng (Science and Knowledge Research Society, 2014)
Satellite communications (SatCom) can offer rapid establishment of voice and data connectivity. The unique potentials of satellite communications are well suited to fill certain breach of contacts during catastrophic incidents and also in isolated places critical for military operation. Military satellite communication is designed to comprise highly steadfast delivery of voice, data and video services between military headquarters and field units. The paper briefly outlines the importance of such facility. The paper highlights an important concern pertaining to the performance predictions of the military X-band satellite communication link especially when facing challenges due to severe rain attenuation in tropical countries. It is proposed that a prediction technique can be employed as well as data acquired from meteorological radars can be exploited to provide estimations of required fade margin for the satellite link.